Analisis Kebutuhan Pengembangan Pembelajaran Ekonomi Berbasis Virtual Reality - Muhammad Basri; Achmadi, Achmadi; Fikri Abdillah; Muhammad Rifai Irfan (Journal Pendidikan Ilmu Pengetahuan Sosial, 2025)
Current economics learning practices are predominantly reliant on two-dimensional media such as PowerPoint and Canva, which often fail to visualize abstract economic concepts effectively. This limitation reduces student engagement and understanding of real-world economic contexts. This study aims to analyze the specific needs for developing Virtual Reality (VR)-based economics learning media. Using a qualitative descriptive approach, data were collected through semi-structured interviews and documentation from Economics teachers and High School students in Pontianak City and Kubu Raya Regency. The data were analyzed using an interactive model comprising data condensation, display, and verification. The results indicate a significant gap between the static media currently used and the students' need for immersive learning experiences. Specifically, teachers and students identified a critical need for VR simulations to visualize complex topics such as Market Mechanisms, International Trade, and Stock Exchanges. Furthermore, the study highlights that successful VR implementation requires user-friendly interfaces and compatibility with existing school infrastructure. These findings serve as a foundational reference for developing valid and practical VR media to enhance critical thinking and learning motivation in Economics